Project-Based Learning and Higher-Order Thinking Skills in EFL Contexts: A Systematic Review - Nursita Nursita; Sri Setyarini; Iyen Nurlaelawati (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2026)
This study examined the implementation of Project-Based Learning (PjBL) in English as a Foreign Language (EFL) contexts to promote Higher-Order Thinking Skills (HOTS). A Systematic Literature Review (SLR) was conducted on 25 empirical studies published between 2021 and 2026 using predefined inclusion criteria and the PRISMA framework. The reviewed studies indicate that PjBL is frequently associated with the development of HOTS, particularly critical thinking (72%), followed by creativity (28%) and problem-solving (20%). The review identified five major categories of project outputs, including digital projects, performance-based tasks, academic writing, creative-cultural works, and integrated classroom projects. Rubric-based assessment emerged as the most commonly used assessment method, although assessment practices remained inconsistent across studies. Several studies also reported challenges related to time constraints, teacher readiness, and variations in implementation strategies. In addition, PjBL was commonly integrated with technology-based and collaborative learning approaches in EFL classrooms. This review contributes to the literature by synthesizing patterns of HOTS development, project output types, assessment practices, and instructional integration in PjBL-based EFL learning. Overall, the findings highlight the need for more balanced HOTS-oriented task design, clearer assessment frameworks, and more consistent implementation practices.